Synergistic bioconversion of lipids and carotenoids from food waste by Dunaliella salina with fulvic acid via a two-stage cultivation strategy. (15th April 2021) - Wang, Xiang; Zhang, Man-Man; Liu, Si-Fen; Xu, Rui-Lan; Mou, Jin-Hua; Qin, Zi-Hao; Zhou, Zhi-Gang; Li, Hong-Ye; Lin, Carol Sze Ki; Sun, Zheng
Graphical abstract: Highlights: Glucose was preferred as an organic carbon source in Dunaliella salina fermentation. Food waste hydrolysate was utilized as nutrient source in D. salina cultivation. Food waste derived algal biomass was rich in lipid and carotenoid. Fulvic acid alleviated oxidative stress to improve lipid and carotenoid biosynthesis. Abstract: Dunaliella salina is a promising microbial host for the sustainable production of bioenergy and valuable compounds. D. salina can be mixotrophically cultivated using a pure organic carbon source. However, pure organic carbon sources remarkably enhance the cost of cultivation and constrain the development of upscale microalgal cultivation. This study examined the feasibility of using low-value food waste supplemented with fulvic acid in D. salina mixotrophic cultivation for lipid and carotenoid accumulation. The glucose-rich hydrolysate was first obtained via enzymatic hydrolysis from selected food waste. This hydrolysate was an appropriate source of organic carbon for microalgal mixotrophy based on a two-stage cultivation strategy for investigating the biomass and accumulation of valuable products. In addition, fulvic acid, which contains oxygen-rich and carbon-poor functional groups, was used in the second stage to maximise the production of biomass (3.1 ± 0.2 g/L), lipids (0.75 ± 0.03 g/L) and carotenoids (0.52 ± 0.03 g/L). The biodiesel quality of the lipid derived from D. salina biomass based on food waste hydrolysate met the previously approved standards. These data illustrate a sustainable and efficient algal-based food waste biorefinery strategy for the co-production of bioenergy and bioactive compounds, and offer key insights to address the issues of global food waste and algal-based resource utilisation.